EFFECTS OF FERMENTED GOAT'S MILK ADDED LEAF PANDAN FILTRATE ON ESCHERICHIA COLI - Nafis, Muhammad; Nurliana, Nurliana; Sutriana, Amalia; Sugito, Sugito; Dasrul, Dasrul (Buletin Veteriner Udayana, 2023)
Probiotics and herbs have potential as antibacterials. This study aims to determine the activity, inhibitory, and bactericidal effect of Lactobacillus casei fermented goat's milk added with fragrant pandan leaf filtrate at different concentrations to Escherichia coli. This study used a completely randomized design (CRD) type of post-test only control group design consisting of 8 (eight) treatments. Group P0 used distilled water (negative control) and group P1 used chloramphenicol (positive control). Lactbacillus casei roasted goat's milk was added with fragrant pandan filtrate at concentrations of 17.5%, 22.5%, 27.5%, and 32.5% in groups P2, P3, P4, and P5. Group P6 only used boiled milk and P7 only used fragrant pandan filtrate. Analysis of variance showed that the addition of fragrant pandan leaf filtrate to fermented goat's milk had no significant effect (P>0,05) among varied concentration groups, but had a significant effect (P<0,01) compared to the negative, positive, and comparative (fragrant pandan leaf filtrate) control groups. The results of the inhibitory and bactericidal effect showed that fermented goat's milk added with fragrant pandan leaf filtrate had the ability to inhibit and kill E . coli colonies. As conclusion, L . casei fermented goat's milk added with fragrant pandan leaf filtrate with varied concentrations has the weak antibacterial activity against E . coli